Rabbi Judah Moscato and the Jewish Intellectual World of Mantua in the 16th-17th Centuries - Veltri, Giuseppe; Miletto, Gianfranco (Leiden : BRILL, 2012)
Judah ben Joseph Moscato (c.1533-1590) was one of the most distinguished rabbis, authors, and preachers of the Italian-Jewish Renaissance. This volume is a record of the proceedings of an international conference organized in Mantua and consists of contributions on Moscato and his intellectual world.
12. Some Unknown 16th-Century Documents about Abraham Yagel and a Possible Link to the Controversy about the "Holy Diana" in the Mantuan Synagogue13. On Abraham's Neck. The Editio Princeps of the Sefer Yesirah (Mantua 1562) and Its Context; 14. The Italian Translation of the Psalms by Judah Sommo; 15. Savants and Scholars in Jewish Mantua: A Reassessment; Bibliography; Subject Index.
Description based on print version record.
Keywords: Moscato, Judah ben Joseph, -- ca. 1530-ca. 1593 -- Congresses; Rabbis -- Italy -- Mantua -- Biography -- Congresses; Jews -- Italy -- Mantua -- Intellectual life -- 16th century -- Congresses; Jews -- Italy -- Mantua -- Intellectual life -- 17th century -- Congresses; Jews -- Italy -- Mantua -- Intellectual life -- 16th century -- Congresses; Moscato, Judah ben Joseph, ca. 1530-ca. 1593 -- Congresses; Moscato, Judah ben Joseph, ca. 1530-ca. 1593.; Rabbis -- Italy -- Mantua -- Biography -- Congresses; RELIGION / Judaism / History; Electronic books